Examining Researcher Needs and Barriers for using Electronic Health Data for Translational Research - Stephens, Kari A. (AMIA Jt Summits Transl Sci Proc, 2015)
To achieve the Learning Health Care System, we must harness electronic health data (EHD) by providing effective tools for researchers to access data efficiently. EHD is proliferating and researchers are relying on these data to pioneer discovery. Tools must be user-centric to ensure their utility. To this end, we conducted a qualitative study to assess researcher needs and barriers to using EHD. Researchers expressed the need to be confident about the data and have easy access, a clear process for exploration and access, and adequate resources, while barriers included difficulties in finding datasets, usability of the data, cumbersome processes, and lack of resources. These needs and barriers can inform the design process for innovating tools to increase utility of EHD. Understanding researcher needs is key to building effective user-centered EHD tools to support translational research.